Growth Hormone (GH) Deficient Mice With GHRH Gene Ablation Are Severely Deficient in Vaccine and Immune Responses Against Streptococcus pneumoniae - Farhat, Khalil; Bodart, Gwennaëlle; Charlet-Renard, Chantal; Desmet, Christophe J.; Moutschen, Michel; Beguin, Yves; Baron, Frédéric; Melin, Pierrette; Quatresooz, Pascale; Parent, Anne-Simone; Desmecht, Daniel; Sirard, Jean-Claude; et al. (Frontiers in Immunology, 2018)
The precise impact of the somatotrope axis upon the immune system is still highly debated. We have previously shown that mice with generalized ablation of growth hormone (GH) releasing hormone (GHRH) gene (Ghrh-/-) have normal thymus and T-cell development, but present a marked spleen atrophy and B-cell lymphopenia. Therefore, in this paper we have investigated vaccinal and anti-infectious responses of Ghrh-/- mice against S. pneumoniae, a pathogen carrying T-independent antigens. Ghrh-/- mice were unable to trigger production of specific IgM after vaccination with either native pneumococcal polysaccharides (PPS, PPV23) or protein-PPS conjugate (PCV13). GH supplementation of Ghrh-/- mice restored IgM response to PPV23 vaccine but not to PCV13 suggesting that GH could exert a specific impact on the spleen marginal zone that is strongly implicated in T-independent response against pneumococcal polysaccharides. As expected, after administration of low dose of S. pneumoniae, wild type (WT) completely cleared bacteria after 24 h. In marked contrast, Ghrh-/- mice exhibited a dramatic susceptibility to S. pneumoniae infection with a time-dependent increase in lung bacterial load and a lethal bacteraemia already after 24 h. Lungs of infected Ghrh-/- mice were massively infiltrated by inflammatory macrophages and neutrophils, while lung B cells were markedly decreased. The inflammatory transcripts signature was significantly elevated in Ghrh-/- mice. In this animal model, the somatotrope GHRH/GH/IGF1 axis plays a vital and unsuspected role in vaccine and immunological defense against S. pneumoniae.